Micro- and Nanoplastics Produced from Textile Finishes: A Review - Ali, Azam; Qamer, Shafqat; Shahid, Muhammad; Tomkova, Blanka; Khan, Muhammad Zaman; Militky, Jiri; Wiener, Jakub; Venkataraman, Mohanapriya (Langmuir, 2024)
The problem of increasing plastic pollution has emerged as a significant societal issue. Plastics can originate from various sources, and there is growing concern among researchers to study and investigate this new category of pollution. The plastic waste is found at the macro, micro, and nanoscale, and its study has had great significance according to the perspective of posing hazardous impacts on living organisms. Given the high demand for functional textiles, the textile industries are supporting the coating of different polymeric based finishes on the surface of textile products. The plastic debris emitted from these coated finishes are in the ranges of nanometric scale, so-called polymeric nanoplastics (PNPs). With the new terminology, polymeric nanoplastics (PNPs) released from textile finishes or coatings are being increasingly mentioned, and the term fibrous microplastics (FMPs) can be seen as outdated. This study is based on an intensive review of a very novel category of debris plastics (PNPs) mostly produced from textile finishes or coatings. In fact, FMPs and PNPs released from synthetic textiles and textiles coated with plastic-based finishes during washing activities are considered to be a major cause that contributes to the current overall load of microplastics (MPs) in the environment. A link between the concentration of NPs from textile fibers and NPs from textile polymeric-based coatings in freshwater and sediments within a particular local setting and the extent of activities of the textile industry has been demonstrated. Invested efforts have been paid to consider and concentrate on plastic pollution (nanoplastics from textile polymeric coatings). We also summarize existing methodologies to elucidate the identification and proactive quantification of nanoplastics shed from the textile polymeric coatings. To this end, more than 40 studies have been done to identify the physical, chemical, and mechanical parameters and to characterize nanoplastics.